2005
DOI: 10.1085/jgp.200509355
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Ca2+ Signaling in the IsolatedCaenorhabditis elegansIntestine

Abstract: Defecation in the nematode Caenorhabditis elegans is a readily observable ultradian behavioral rhythm that occurs once every 45-50 s and is mediated in part by posterior body wall muscle contraction (pBoc). pBoc is not regulated by neural input but instead is likely controlled by rhythmic Ca 2 ϩ oscillations in the intestinal epithelium. We developed an isolated nematode intestine preparation that allows combined physiological, genetic, and molecular characterization of oscillatory Ca 2 ϩ signaling. Isolated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 56 publications
4
94
0
1
Order By: Relevance
“…In addition, we found that RNAi of two endogenous targets, elt-2 and pept-1 , induced robust phenotypes in two different rrf-1 mutants. While elt-2 RNAi seemed to play an exclusively intestinal-specific role, pept-1 RNAi induced effects in both intestinally and hypodermally rescued rde-1 strains [12], [13]. This result may indicate that pept-1 functions as an oligopeptide transporter not only in the intestine, but also in the hypodermis.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we found that RNAi of two endogenous targets, elt-2 and pept-1 , induced robust phenotypes in two different rrf-1 mutants. While elt-2 RNAi seemed to play an exclusively intestinal-specific role, pept-1 RNAi induced effects in both intestinally and hypodermally rescued rde-1 strains [12], [13]. This result may indicate that pept-1 functions as an oligopeptide transporter not only in the intestine, but also in the hypodermis.…”
Section: Discussionmentioning
confidence: 90%
“…Expression was also noticed in some neurons but is excluded from the intestine. To find tissues where knocking down of mekk-3 is sufficient to extend lifespan, we used tissue-specific RNAi systems (Espelt et al ., 2005; Qadota et al ., 2007). Interestingly, we found that mekk-3 RNAi did not extend lifespan when specifically knocked down in the intestine, the major metabolic tissue in the worm.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the tissue-specific activity of other genes in the insulin signaling pathway in regulating GO toxicity, we performed intestine-specific RNAi on the VP303 strain33. In nematodes, we found that intestine-specific RNAi of the daf-2, age-1, akt-1 , or akt-2 gene resulted in prolonged lifespan, whereas intestine-specific RNAi of the daf-16 or daf-18 gene led to reduced lifespan (Fig.…”
Section: Resultsmentioning
confidence: 99%